2017
DOI: 10.1038/s41598-017-17830-z
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gut Microbiota Profiles in Sows and Neonatal Piglets Associated with Porcine Epidemic Diarrhea Virus Infection

Abstract: Porcine epidemic diarrhea virus (PEDV) is a devastating cause of diarrhea in pigs worldwide. Most of studies have focused on molecular and pathogenic characterization of PEDV, whereas there were limited studies in understanding the role of gut microbiota (GM) in viral-associated diarrhea. Here, using the Illumina MiSeq platform, we examined and compared the impact of PEDV infection on the GM of sows and their piglets less than 10 days old. Our results showed that PEDV caused alternations in the structure and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 58 publications
8
40
0
1
Order By: Relevance
“…This sensitivity may generate individual differences in microorganisms, even in piglets from the same cohort [35]. Here, we found that PEDV infection significantly altered the gut microbiota in piglets, an outcome that was confirmed in several other studies [20][21][22][23].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This sensitivity may generate individual differences in microorganisms, even in piglets from the same cohort [35]. Here, we found that PEDV infection significantly altered the gut microbiota in piglets, an outcome that was confirmed in several other studies [20][21][22][23].…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we successfully demonstrated that the microbial community structure of colonic mucosa and content differed significantly between healthy and PEDV-infected piglets. Likewise, previous research has shown that the proportions of Escherichia-Shigella, Enterococcus, Fusobacterium, and Veillonella increased significantly in PEDV-infected piglets, while those of short-chain fatty acid (SCFA)-producing bacteria (e.g., Rikenellaceae_RC9_gut_group, Butyricimonas, and Alistipes) underwent a decrease [21]. Moreover, the gut microbiota of PEDV-infected piglets was shown to exhibit significant changes at the genus and phylum levels [22] that are likely to disrupt microecological homeostasis.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In pigs, several studies have reported that there exists a close relationship between diarrhea-relating coronaviruses and intestinal microbiota (Huang et al, 2018;Liu et al, 2015;Song et al, 2017;Tan et al, 2019). It has been reported that PEDV infection induced gut microbial dysbiosis, leading to a reduction in beneficial bacteria and an increase in pathogenic bacteria.…”
mentioning
confidence: 99%